2018
DOI: 10.21273/hortsci12644-17
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Honey Bee Hive Densities Promotes Pollination and Yield Components of Highbush Blueberry in Western Washington

Abstract: Yield components including fruit set and berry size in northern highbush blueberry (Vaccinium corymbosum) can be limited in key production regions like western Washington. Climactic conditions influence the activity levels of blueberry’s primary commercial pollinator, honey bee (Apis mellifera). Cool springs with frequent rainfall, which are common during the spring bloom period in western Washington, can reduce honey bee activity, pollination effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
8
3
Order By: Relevance
“…In our study, minimum seed number also varied greatly among cultivars. In Washington, Arrington and DeVetter (2018) found fewer seeds/berry in 'Duke' (11-33) than in our study, but also reported lower fruit set in their region, likely because of adverse weather reducing pollinator activity (Arrington and DeVetter, 2017). Increased pollinator activity through stocking with more hives/ha increased seeds/berry (Arrington and DeVetter, 2018).…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…In our study, minimum seed number also varied greatly among cultivars. In Washington, Arrington and DeVetter (2018) found fewer seeds/berry in 'Duke' (11-33) than in our study, but also reported lower fruit set in their region, likely because of adverse weather reducing pollinator activity (Arrington and DeVetter, 2017). Increased pollinator activity through stocking with more hives/ha increased seeds/berry (Arrington and DeVetter, 2018).…”
Section: Resultscontrasting
confidence: 55%
“…In Washington, Arrington and DeVetter (2018) found fewer seeds/berry in 'Duke' (11-33) than in our study, but also reported lower fruit set in their region, likely because of adverse weather reducing pollinator activity (Arrington and DeVetter, 2017). Increased pollinator activity through stocking with more hives/ha increased seeds/berry (Arrington and DeVetter, 2018). Although Ehlenfeldt and Martin (2010) reported that an early-ripening cultivar had fewer seeds and smaller berries than a later ripening cultivar, we found no such relationship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both this study and Arrington & De Vetter (2018) found that flower visitation did not predict yield like other studies suggest (Isaacs & Kirk, 2010). These results are different from those observed on lowbush blueberry (Aras, De Oliveira & Savoie, 1996) and rabbiteye blueberry (Vaccinium virgatum var.…”
Section: Discussioncontrasting
confidence: 44%
“…A key limitation of this study is that while Arrington & De Vetter (2018) randomized the stocking rate to fields, findings in this study are correlational and depended on variation within commercial production systems. Future studies should control for colony strength by randomly assigning strong and weak colonies to different fields.…”
Section: Discussionmentioning
confidence: 93%